Mushroom-based cosmeceutical ingredients: Microencapsulation and in vitro release profile - Taofiq, Oludemi (2018)
Mushrooms can be used as a source of cosmeceutical ingredients. Agaricus bisporus and Pleurotus ostreatus ethanolic extracts present important bioactive properties, but withsome compounds showingeasy oxidation and degradation. In the present work, microencapsulation by atomization/coagulation technique was used toprotect the extracts. The obtained microspheres were characterised in terms of morphology, particle size distribution and encapsulation eﬃciency. Microencapsulated extracts were incorporated into a semi-solid base cream and their performance compared with the use of the free forms in terms of bioactivity, and in vitro release using the cosmetic matrix and real time conditions (up to 6 months). The physico-chemical properties (colour and pH) of the developed formulations were also monitored over the same time period. The cosmeceutical formulations containing free extracts displayed bioactivity. For the formulations prepared with the encapsulated forms, the release of the extracts was achieved and anti-tyrosinase and antimicrobial activities were observed, while for the antioxidant activity, the extract release over the time was not suﬃcient to exert an eﬀect. Overall, the use of mushroom extracts in free or encapsulated forms can be an option in cosmeceutical formulations, and the encapsulated forms can allow a controlled release leading to bioactivity control.